2002
DOI: 10.1042/bst0300495
|View full text |Cite
|
Sign up to set email alerts
|

The contrasting IgG-binding interactions of human and herpes simplex virus Fc receptors

Abstract: A virally encoded, high-affinity Fc receptor (FcR) is found on herpes simplex virus type 1 (HSV-1) particles and infected cells where its binding of non-immune IgG protects cells from host-mediated lysis. Whilst mutation or aglycosylation of the IgG CH2 domain reduced binding to human FcR, the interaction with HSV-1 FcR was not affected. However, the HSV-1 FcR, unlike human FcR, discriminates between human IgG1 allotypes, being sensitive to changes at positions 214 (CH1) and 356/358 (CH3), away from its propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 5 publications
0
12
0
1
Order By: Relevance
“…We engineered J10 into a human IgG2deltaA (Armour et al, 2002) and chain antibody and further improved its antigen binding affinity. The resulting antibody, J16, contains fully human sequence outside of the complementarity determining regions.…”
Section: Resultsmentioning
confidence: 99%
“…We engineered J10 into a human IgG2deltaA (Armour et al, 2002) and chain antibody and further improved its antigen binding affinity. The resulting antibody, J16, contains fully human sequence outside of the complementarity determining regions.…”
Section: Resultsmentioning
confidence: 99%
“…This work demonstrated that the G2Da constant region, which incorporates IgG4 residues at positions 330 and 331 within the CH2 domain, showed no detectable binding to FccRI and FccRIII and reduced binding to FccRII [20,26,31]. G2Da antibodies did not activate human monocytes or trigger CD16 + NK cellmediated cytotoxicity (ADCC).…”
Section: Discussionmentioning
confidence: 96%
“…Secondly, all natural IgG subclasses have the capacity to recruit at least some of the human effector systems, a property detrimental to an antibody targeted to the vascular endothelial cells at sites of inflammation. For the chimeric antibodies, we chose a modified human 2D10 IgG2 constant region that has minimal interactions with effector molecules (G2Da, [26]). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Es más, gE posee un dominio proteico con homología a receptores del hospedero llamados FcγRs, los cuales son expresados en la superficie de células inmunes y median la captura y degradación de microbios opsonizados (complejos antígeno-anticuerpo o complejos inmunes) a través de la unión a la porción Fc de los anticuerpos [121][122][123] . Con ello, las glicoproteínas gE de VHS evitarían, tanto la acción del complemento, como la fagocitosis vía receptores FcγRs por células inmunes.…”
Section: Evasión De La Respuesta Inmune Humoralunclassified